Spherically Symmetric Wormhole Gravitational Lens Deflection Angle Signifying Braneworld Cosmology *Supported by the Short-Term Research Grant Awarded of University of Malaya. (June 2017) - Alias, Anuar; Wan Abdullah, Wan Ahmad Tajuddin
Abstract : Previously, the gravitational lens of a wormhole was introduced by various researchers. Their treatment was focused basically on the lens signature that describes wormhole geometrical character such as the differences from a black hole or between any various types of wormhole models. The braneworld scenario provides the idea of spacetime with underlying extra-dimensions. The inclusion of extra-dimensional terms in the lens object spacetime line element will result in some variation in the expression for its gravitational lens deflection angle. Thus in this paper we investigate such variation by deriving this deflection angle expression. As such, this paper not only shows the existence of such variation but also suggests the potential utilization of gravitational lensing to prove the existence of extra dimensions by studying the deflection angle characteristic in accordance with the spacetime expansion rate of the universe.